Kegiatan senam kaki terhadap penurunan kadar gula darah pada lansia dengan diabetes melitus Di Desa Air Satan Kabupaten Musi Rawas - Soewito, Bambang; Susmini, Susmini; Wijaya, Sapondra; Wibowo, Wahyu Dwi Ari; Supriyanto, Eko; Ulfa, Msy Hartina; Martini, Sri; Trisna, Efa (Penamas: Journal of Community Service, 2024)
The increase in blood sugar is a common effect of uncontrolled diabetes mellitus (DM), which can cause serious damage to the nervous system and blood vessels over time. Research shows that due to time constraints, DM patients often have difficulty engaging in physical activities. Diabetic foot exercises have been recommended as a physical activity that can be done anytime and anywhere, including while relaxing with family. These simple exercises can help improve blood circulation, strengthen the small muscles in the feet, prevent foot deformities, and address the limited insulin levels in DM patients. This activity aims to introduce foot exercises to the community, particularly the elderly with DM issues so that they can engage in physical activity despite physical and time limitations. The method involves conducting simulations and health education three times a week. The results showed decreased blood sugar levels in the elderly who participated in this foot exercise program. Hopefully, these foot exercise activities can become an alternative and regular option, especially for the elderly in Ari Satan, Musi Rawas Regency.